A study of mortality and morbidity profile of electrolyte imbalance in critically ill children with special importance to mechanical ventilation - V., Kishore S.; Routray, Mrutyunjay; Champatiray, Jyotiranjan; Satpathy, Saroj Kumar (International Journal of Contemporary Pediatrics, 2019)
Background: Electrolytes imbalance is not uncommon in critically ill children. The outcome of critically ill child is dependent on various factors like the underlying disease, fluid and nutrition, which are responsible for electrolyte homeostasis in tandem with renal function and many others. In this study authors look into morbidity and mortality associated with dyselectrolytemia with special importance to children on mechanical ventilation. Methods: This prospective observational study was conducted in the PICU, SVPPGIP (SCB MC and Hospital), Cuttack during the period November 2015 to October 2017. Includes children admitted to PICU (Based on consensus guidelines for PICUs in India, Indian Society of Critical Care Medicine (Pediatric Section) and Indian Academy of Pediatrics (Intensive Care Chapter). Results: Mortality distribution in electrolyte abnormality patients is 27.9% (around 3 times higher than normal electrolyte patients). 25% hyponatremic patients and 31.25% hypernatremia patients expired, 30.76% hypokalemia patients, 32.72% hyperkalemia patients expired. Morbidity distribution in electrolyte imbalance population was 85.27%, with more than 7 days of stay in PICU. Amongst the mechanical ventilated patient, 54.23% patients having potassium disturbances were associated with significant mortality and morbidity. No such significant relation exists between mechanical ventilation and dyselectrolytemia of sodium and calcium. Conclusions: Early recognition with a thorough understanding of common electrolyte abnormalities and their prompt management definitely pose an implication on the final outcome of the patient. Aggressive and strict adherence to correction of in particular to potassium before weaning is necessary for successful weaning from ventilator.